Delusional suicide behavior of patients with schizophrenia and methods of its prevention - Raspopova, Natalya; Panov, Evgeny (Medical and Health Science Journal, 2011)
The study involved 320 patients with schizophrenia hospitalized in a psychiatric hospital in connection with various forms of suicidal behavior. The study developed a typology of mechanisms of suicidal behavior of schizophrenics. Analysis of the experience of the Zyprexa (olanzapine) when treating patients with schizophrenia with delusional motivation for suicidal behavior has shown that the drug provides enduring reduction of delusional disorders and reduces the risk of recurrent suicidal behavior.
Keywords: psychiatrické oddělení nemocnice; chování a mechanismy chování; schizofrenie; Antipsychotic Agents; Observational Studies as Topic; pozorovací studie jako téma; antipsychotika; sebevražda; Psychiatric Department, Hospital; Humans; lidé; Schizophrenia; Behavior and Behavior Mechanisms; Suicide